Different Methods of Grape Propagation: A Review - Atif, Mudir; Samadi, Ghulam Rasoul (Journal of Natural Sciences – Kabul University, 2025)
Grapevine (Vitis vinifera L.) belongs to the Vitaceae family. It can be propagated through various methods, depending on the intended purpose. If the aim is to develop new varieties or introduce desirable traits into existing ones, sexual propagation (seed) is employed. However, when the goal is to propagate plants in pest- and disease-free soil, hardwood cuttings are preferred, as they enable the plants to reach the fruit-bearing stage more quickly and improve both yield and fruit quality. The vinifera species of grape is highly susceptible to phylloxera insects and fungal diseases. Therefore, in regions where these problems are common, grafting on resistance rootstock is widely used. In vineyards, layering is practiced to replace dried or dead vines. Additionally, if adequate cold storage and laboratory facilities are available, propagation through plant tissue culture is a viable method. Depending on the specific propagation goal, growers can select the most suitable technique from the options mentioned above.